Nilai-nilai Pendidikan dalam Pappaseng Bugis sebagai Penguatan Karakter Peserta Didik: Penelitian - Ita Rosvita; Nur Annisa Fitri; Ilma Rahim (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Character Building is a national education initiative in Indonesia that aims to develop and strengthen students' character. This program is designed to create individuals who not only excel academically but also possess strong integrity and are prepared to become responsible citizens. Character education involves developing the potential to cultivate positive behavior. If character education is implemented in all schools, it can help students become honest, polite, and responsible individuals who believe in Almighty God. One method to intentionally foster student character is through the introduction, understanding, and application of local values ​​or regional cultures, such as the Bugis culture with its meaningful Lontara script. One form of the Bugis Lontara script that is associated with wisdom and rich in values ​​and character is Pappaseng. Pappaseng contains great ideas, noble thoughts, valuable spiritual experiences, and considerations to guide students' current character behavior. Pappaseng is a Bugis cultural heritage in the form of messages, advice, or wisdom passed down orally and in writing by parents and wise figures of the past. Pappaseng contains noble values ​​such as honesty (lempu'), responsibility, courage, hard work, and respect for others and the environment, which function as guidelines for life for the Bugis people era.